Efectos económicos de la transición energética en la exportación de petróleo en Colombia. (2020)
The document aims to demonstrate the impact of the energy transition on the Colombian economy with the help of the MICMAC program, which is a prospective method technique. The energy transition that is currently being experienced seeks to change its energy system, from non-renewable energy to renewable energy, this change is important due to the consequences that the planet is experiencing, in addition to the demand for non-renewable resources has made its reserves every may be reduced, until reaching the point of exhaustion, so that it is absolutely necessary to look for new sources and implement new alternatives.